2003
DOI: 10.1590/s1516-89132003000200009
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase and lipid peroxidation of soybean roots in response to p-coumaric and p-hydroxybenzoic acids

Abstract: The scope of the present study was to investigate how the p-coumaric (p-CA) and p-hydroxybenzoic (p-HD) acids affect the peroxidase (POD, EC 1.11.1.7) activity, the lipid peroxidation (LP) and the root growth of soybean (Glycine max (L.) Merr.). Three-day-old seedlings were cultivated in nutrient solution containing p-CA or p-HD (0.1 to 1 mM) for 48 h. After uptake, both compounds (at 0.5 and 1 mM) decreased root length (RL), fresh weight (FW) and dry weight (DW

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
0
29
0
1
Order By: Relevance
“…Hydrogen peroxide accumulation further enhances lipid peroxidation and results in the disruption of cell metabolism, leading to cell death (Stone and Yang 2006). A number of studies have indicated that phenolic acids, including CA, affect membrane permeability and thus affect plant growth (Baziramakenga et al 1995;Doblinski et al 2003;Ju et al 2007). Baziramakenga et al (1995) demonstrated that benzoic and cinnamic acids induced ROS generation, which severely affected the integrity of the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide accumulation further enhances lipid peroxidation and results in the disruption of cell metabolism, leading to cell death (Stone and Yang 2006). A number of studies have indicated that phenolic acids, including CA, affect membrane permeability and thus affect plant growth (Baziramakenga et al 1995;Doblinski et al 2003;Ju et al 2007). Baziramakenga et al (1995) demonstrated that benzoic and cinnamic acids induced ROS generation, which severely affected the integrity of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Baziramakenga et al (1995) demonstrated that benzoic and cinnamic acids induced ROS generation, which severely affected the integrity of the membrane. Doblinski et al (2003) reported that p-coumaric and p-hydroxybenzoic acids (0.5-1.0 mM) caused lipid peroxidation in soybean roots, resulting in growth inhibition. Caffeic acid is also known to alter root activity by depolarizing the root membrane (Glass and Dunlop 1974); however, the mechanism by which this occurs involves ROS is not still clear.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of flavanones in benzoic acid and their derivatives has been previously reported (Barz and Hoesel, 1979), and the non-enzymatic cleavage of naringenin produces p-hydroxybenzoic acid (Newhall and Ting, 1967). The potential of this phenolic compound to be allelopathic has been widely reported (Politycka, 1996;Doblinski et al, 2003;Inderjit and Duke, 2003;Weir et al, 2004). In agreement with this, enhanced quercetin autooxidation leads to the formation of the 3,4-dihydroxybenzoic acid (Takahama and Hirota, 2000).…”
Section: Discussionmentioning
confidence: 64%
“…The extract was centrifuged (10,000 £ g, 15 min, 4 C), and the supernatant was used to determine the content of MDA. 32 An aliquot of 0.5 ml of the supernatant was added to 4 ml of 0.5% of thiobarbituric acid (prepared in 20% of trichloroacetic acid). The mixture was heated in boiling water for 10 min and then quickly cooled in an ice-bath; samples were then centrifuged (3,500 £ g, 5 min).…”
Section: Lipid Peroxidationmentioning
confidence: 99%